Efforts to Improve Learning Outcomes Through Smart Board Media in Pancasila Education Subjects for Second Grade Students - Oknita, Eva; Apriani, Ria; Hotnida, Denny (JENTIK : Jurnal Pendidikan Teknologi Informasi dan Komunikasi, 2024)
The purpose of community service is to make a real and positive contribution to society through various useful activities. The learning outcomes of second-grade students at SD Negeri 37 Bengkulu City in Pancasila Education are still low. During the learning process, students tend not to pay attention to the teacher's explanations. This is due to the teacher-centered learning process, which results in poor student learning outcomes. This study aims to improve the learning outcomes of second-grade students in Pancasila Education subjects at SD Negeri 37 Bengkulu City through the implementation of Smart Board media. This research is a classroom action research (CAR) that consists of two cycles. Each cycle consists of four stages: planning, action implementation, observation, and reflection. The subjects of this study were 20 second-grade students. Data collection techniques were conducted through tests (formative tests) and non-tests (observation and documentation). In the pre-cycle, the percentage of student mastery was 40% or 8 students; in cycle I, student mastery increased to 70% or 14 students; and in cycle II, the percentage of student mastery almost reached perfection at 90% or 18 students out of a total of 20 students. It can be concluded that Pancasila Education using Smart Board media can improve the learning outcomes of second-grade students at SD Negeri 37 Bengkulu City.